Body mass index, dental caries and sugar intake in 2-5 year-old preschoolers - Martins, Ronald Jefferson (2014)
AIM: To determine the association between dental caries, Body Mass Index (BMI) and sugar intake in children attending primary school. METHODS: A cross-sectional study was conducted with 91 children, with mean age of 3.9 years (sd = ±1.0), considering anthropometric measurements, according to standardized methodology of the Ministry of Health and occurrence of dental caries was recorded from clinical examinations (dmft). The sugar intake level was measured with a questionnaire that was applied to parents/caretakers of the children. The association of the variables was checked using a correlation with the Contingency C coefficient test. RESULTS: 33 (36.3%) children were at risk for overweight, overweight or obese. Of these, 10 (30.3%) had dmft >1. An association was found between sugar added to the bottle and child dmft (coeff. C = 0.5853 and p <0.0001) and also with BMI (coeff. C = 0.5693 and p <0.0001). There was no association between BMI and caries (chi-square = 0.1447 and p-value = 0.7036). CONCLUSIONS: It was concluded that there was a correlation between sugar intake and dmft and BMI, but not between caries and BMI.